Transport proteins determine drug sensitivity and resistance in a protozoan parasite, Trypanosoma brucei - Munday, Jane C.; Settimo, Luca; de Koning, Harry P. (Frontiers in Pharmacology, 2015)
Drug resistance in pathogenic protozoa is very often caused by changes to the ‘transportome’ of the parasites. In Trypanosoma brucei, several transporters have been implicated in uptake of the main classes of drugs, diamidines and melaminophenyl arsenicals. The resistance mechanism had been thought to be due to loss of a transporter known to carry both types of agents: the aminopurine transporter P2, encoded by the gene TbAT1. However, although loss of P2 activity is well-documented as the cause of resistance to the veterinary diamidine diminazene aceturate (Berenil®), cross-resistance between the human-use arsenical melarsoprol and the diamidine pentamidine (MPXR) is the result of loss of a separate High Affinity Pentamidine Transporter (HAPT1). A genome-wide RNAi library screen for resistance to pentamidine, published in 2012, gave the key to the genetic identity of HAPT1 by linking the phenomenon to a locus that contains the closely related T. brucei aquaglyceroporin genes TbAQP2 and TbAQP3. Further analysis determined that knockdown of only one pore, TbAQP2, produced the MPXR phenotype. TbAQP2 is an unconventional aquaglyceroporin with unique residues in the “selectivity region” of the pore, and it was found that in several MPXR lab strains the WT gene was either absent or replaced by a chimeric protein, recombined with parts of TbAQP3. Importantly, wild-type AQP2 was also absent in field isolates of T. b. gambiense, correlating with the outcome of melarsoprol treatment. Expression of a wild-type copy of TbAQP2 in even the most resistant strain completely reversed MPXR and re-introduced HAPT1 function and transport kinetics. Expression of TbAQP2 in Leishmania mexicana introduced a pentamidine transport activity indistinguishable from HAPT1. Although TbAQP2 has been shown to function as a classical aquaglyceroporin it is now clear that it is also a high affinity drug transporter, HAPT1. We discuss here a possible structural rationale for this remarkable ability.